The Role of The Iconic Food Exposure Model: "Warung Tegal" (Warteg) Manuver in the Disaster of the Covid-19 Pandemic in Central Java, Indonesia - Rif’ah Dwi Astuti; Sri - Wahyuni; Andi - Setiawan; Bagus Yunianto Wibowo (Admisi dan Bisnis, 2022)
The COVID-19 pandemic has caused a business in this case Warung Tegal (Warteg) to experience a decline in turnover of up to eighty percent. Warung Tegal (Warteg) as a business unit must change their business orientation to be able to operate under any conditions. This study analyzes the entrepreneurial orientation of companies (Warteg) in various different contexts. Given the existing literature on entrepreneurship, we depart from the hypothesis that the context in which a business operates determines the importance of each dimension comprising the multidimensional concept of entrepreneurial orientation, thereby moderating its influence on marketing performance. The sample for this study consisted of 205 small and medium-sized Warung Tegal (Warteg) companies in Central Java. We tested the hypothesis by measuring the moderating effect of context on the structural equation modeling technique. The results of this study found that the critical moderating role of Iconic Food Exposure strengthens the relationship between Iconic Food Exposure and mediates the relationship between Entrepreneurial Orientation, and Competitive Maneuverability, and that competitive strategy strengthens the relationship between Iconic Food Exposure and Marketing performance.